Telemedicine for screening diabetic retinopathy: The NO BLIND Italian multicenter study. Issue 3 (7th January 2019) - Sasso, Ferdinando Carlo; Pafundi, Pia Clara; Gelso, Aldo; Bono, Valeria; Costagliola, Ciro; Marfella, Raffaele; Sardu, Celestino; Rinaldi, Luca; Galiero, Raffaele; Acierno, Carlo; de Sio, Chiara; Adinolfi, Luigi Elio; et al.
Abstract: Aims: Diabetic retinopathy (DR) represents the main cause of blindness among adults in the industrialized Countries. Use of telemedicine could offer an easy, smart specialist fundus oculi examination, as well as putting in a screening programme many patients who otherwise would be excluded. Materials and methods: The NO BLIND is a transversal, multicentre, observational study. Its pilot phase involved nine public outpatient clinics for 6 months. As endpoint of the study, we assessed the prevalence of DR by retinography in a subset of the Italian population. Patients' fundus oculi photos were performed by trained diabetologists through a digital smart ophthalmoscope. Results: According to our endpoint, in the final study population (n = 1461), obtained excluding patients for whom retinography was not able to provide any diagnosis, DR prevalence was equal to 15.5%. According to the receiver operating characteristic (ROC) curve performed, we can observe how retinography appears a highly accurate method to detect DR (AUROC 0.971, 95% confidence interval, 0.954‐0.989), with a specificity of the 100% and a sensitivity of the 94.3%. Conclusions: Our findings, in an Italian setting, confirm main data in the literature about DR prevalence. Hence, telemedicine could represent an accurate, fast, and cheap method for screening of DR.